The comorbidity of pathological gambling and conversion disorder: case report and the psychotherapy progress - Mortan Sevi, Oya (Journal of Dependence, 2014)
This paper focuses on the psychotherapy process of a pathological gambling dependency case in which a combination of CBT and EMDR techniques was used. A factor that distinguishes this case is the comorbidity of conversion symptoms and their effects in the gambling cycle. The case was 38 year-old man, married and had a daughter. He was admitted to psychotherapy due to the addiction of playing horse racing continued for many years and causing huge financial losses. In addition, he had moderate depressive signs and conversion symptoms. The psychotherapy progress was continued for 12 sessions without medical support because he didn’t benefit from drug treatment continuing for many years. The patient’s desire to gamble and conversion symptoms hadn’t relapsed during 1-year period. This case report underlined that EMDR and CBT are useful treatment options in pathological gambling addiction.